Efektivitas dan Keamanan Terlipressin pada Acute Variceal Haemorhage: Sebuah Kajian Naratif - Steven Victoria Halim; Eko Setiawan (Jurnal Farmasi Indonesia, 2020)
Providing appropriate yet timely treatment to stop bleeding is the key pathway in the management of acute variceal haemorhage (AVH). Several agents can be used to manage bleeding, and one of the new agent recently approved in Indonesia in 2019 is Terlipressin. Information toward the efficacy dan safety of Terlipressin is essentially needed to help optimising effort to use this agent responsibly, specifically in this early phase of entering Indonesian market. This narrative review mainly includes the basic profile, the current updated evidence of the efficacy and safety, the position in the therapy, and the cost of Terlipressin compared with other vasoactive agents. Only systematic review and meta-analysis articles were used to describe the efficacy and safety of Terlipressin considering it were ranked at the top level of evidence-based ladder. Some unique pharmacokinetics and pharmacodynamics properties of Terlipressin, which are not found in other vasoactive, can provide advantages when it is administered to patients in the clinical practice. However, it does not necessarily mean that Terlipression is more superior compared to other vasoactive agents. Findings of our review on three systematic review and meta-analysis found that the efficacy and safety of Terlipressin were not significantly different compared to other vasoactive agents. Therefore, Terlipressin is not the only recommended agent to be used as the first-line vasoactive agent in the management of AVH. Owing to it is relatively new introduced in Indonesia, the cost of using Terlipressin is relatively higher compared to other first-line vasoactive agent. It therefore could be suggested to use Terlipressin only for patients who can attain benefit at most such as patients with contraindications or history of side effect from other vasoactive agents